An overview of ionic liquid degradation by advanced oxidation processes. Issue 16 (18th August 2022) - Mena, Ismael F.; Diaz, Elena; Rodriguez, Juan J.; Mohedano, Angel F.
Abstract: Ionic liquids (ILs) are salts with exceptional properties, such as high thermal stability and low melting point, making them potential substitutes for conventional organic solvents. However, because of their relatively high solubility in water, ILs can enter aquatic systems as pollutants via wastewater discharge. The presence of ILs in the environment is concerning because many ILs have low biodegradability, which can be associated with high ecotoxicity. Crucially, the degradability of ILs is dependent on the nature of their anion and cation components, and many ILs are not readily degraded in conventional wastewater treatment plants and, thus, accumulate in the environment. Therefore, cost-effective solutions to treat these pollutants are required. Advanced oxidation processes (AOPs) are a group of technologies that can remove a wide range of recalcitrant pollutants. In this work, we review the literature concerning IL degradation by AOPs, including Fenton-based systems and photo- and electrochemical treatments, as well as their combinations. The operating conditions, kinetic aspects, and degradation pathways are reviewed. Abstract : UF0001